2009
DOI: 10.1016/j.chembiol.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Permeant Phosphoinositide Derivatives as Modulators of Growth Factor Signaling and Neurite Outgrowth

Abstract: Phosphoinositides are important signaling molecules that govern a large number of cellular processes such as proliferation, differentiation, membrane remodeling, and survival. Here we introduce a fully synthetic membrane-permeant derivative of a novel, easily accessible, and very potent phosphatidylinositol 3,4,5-trisphosphate [PtdIns(3,4,5)P(3)] mimic: phosphatidylinositol 3,4,5,6-tetrakisphosphate [PtdIns(3,4,5,6)P(4)]. The membrane-permeant PtdIns(3,4,5,6)P(4) derivative activated pathways downstream of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
1
25
0
2
Order By: Relevance
“…For example, internalization of β2-adrenergic receptors has been reported to be stimulated by class I PI3K p110γ-mediated PI(3,4,5)P 3 formation [66]. An elegant study using membrane-permeable PI derivatives [101] showed that acute increases of PI(3,4,5)P 3 in the absence of ligand-induced receptor activation trigger the internalization of receptor tyrosine kinases (RTKs). The epidermal growth factor receptor (EGFR) as well as the ephrinA4 receptor, but not GPCRs or the transferrin receptor, was internalized when the cellular concentration of PI(3,4,5)P 3 was increased by either administration of exogenous PI(3,4,5)P 3 or acute recruitment of class I PI3Ks to the plasma membrane [102].…”
Section: Possible Roles For Pi(345)p 3 In Cmementioning
confidence: 98%
“…For example, internalization of β2-adrenergic receptors has been reported to be stimulated by class I PI3K p110γ-mediated PI(3,4,5)P 3 formation [66]. An elegant study using membrane-permeable PI derivatives [101] showed that acute increases of PI(3,4,5)P 3 in the absence of ligand-induced receptor activation trigger the internalization of receptor tyrosine kinases (RTKs). The epidermal growth factor receptor (EGFR) as well as the ephrinA4 receptor, but not GPCRs or the transferrin receptor, was internalized when the cellular concentration of PI(3,4,5)P 3 was increased by either administration of exogenous PI(3,4,5)P 3 or acute recruitment of class I PI3Ks to the plasma membrane [102].…”
Section: Possible Roles For Pi(345)p 3 In Cmementioning
confidence: 98%
“…However, membrane permeable analogs of several PIs have been synthesized and successfully used. Using these compounds it was proven that PI(3,4)P 2 and PI(3,4,5)P 3 directly stimulate the formation of cell protrusions, tyrosine kinase receptor recycling and clathrin-mediated endocytosis [8991]. More recently, these lipid analogs have been employed to show a role of PIs in actomyosin contraction in the developing Drosophila larvae, proving their applicability in in vivo settings [92].…”
Section: Manipulating Phosphoinositide Levelsmentioning
confidence: 99%
“…For example, the addition of aminophospholipid increases endocytosis in living cells (Farge et al 1999) and adding the biologically active isoform, but not other isoforms, of LBPA reduces cholesterol overload in NPC cells (Chevallier et al 2008). Finally, a promising approach has been elaborated by Carsten Schultz and colleagues that developed very elegant strategies to introduce membrane-permeant versions of phosphoinositides into cells so that the lipid is released upon cleavage by cytosolic esterases (Laketa et al 2009;Mentel et al 2011). Such strategies, together with the development of novel chemical biology tools, offer promising new ways to study the function of membrane lipids (Riezman and Johnsson 2011;Wymann and Schultz 2012).…”
Section: Concluding Remarks and Future Challengesmentioning
confidence: 99%